Y'=(x⁴-4x+4)'=4x³-4 1. промежутки возрастания: y'(x)>0, 4x³-4>0, x³-1>0, (x-1)*(x²+x+1)>0 корни: х-1=0 или х²+х+1=0 х=1 или D=-3, корней нет функция у=х⁴-4х+4 возрастает при х∈(1;∞) 2. промежутки убывания: y'(x)<0, (х-1)*(х²+х+1)<0 корни: х-1=0 или х²+х+1=0 х=1 или D=1²-4*1*1=-3<0, корней нет. => x<1 функция убывает при х∈(-∞:1)
1. промежутки возрастания:
y'(x)>0, 4x³-4>0, x³-1>0, (x-1)*(x²+x+1)>0
корни: х-1=0 или х²+х+1=0
х=1 или D=-3, корней нет
функция у=х⁴-4х+4 возрастает при х∈(1;∞)
2. промежутки убывания:
y'(x)<0, (х-1)*(х²+х+1)<0
корни: х-1=0 или х²+х+1=0
х=1 или D=1²-4*1*1=-3<0, корней нет. =>
x<1
функция убывает при х∈(-∞:1)